India - Asean economic relations - Nagesh Kumar (ed.) (New Delhi, 2006)
Indian economy and collectively ten ASEAN members are large and dynamic markets. They are undertaking reforms to deepen their integration within and outside the region.They could fruitfully share technology, capital, human talent, developmental experiences and coordinate their positions in international forums such as WTO negotiations. India-ASEAN partnership could also be an important building bloc of the emerging broader regional economic cooperation in Asia viz. an Asian Economic Community built in a phased manner. Leading experts of the region in their contributions to this book examine the ways in which the emerging partnership between India and ASEAN can be taken forward for mutual benefit, so that the two sides can leverage on each other s strengths to better negotiate the forces of globalization. Specifically, the book addresses the issues concerning the trade liberalization in both regional multilateral contexts. It also deals with the potential of sub-regional cooperation and the strategic implications of India-ASEAN cooperation which have hitherto received insufficient attention in the literature.
Keywords: India - economic conditions